2015
DOI: 10.1007/s10856-015-5649-2
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired soft-tissue adhesive based on poly(diol citrate) with catechol functionality

Abstract: Marine mussels tightly adhering to various underwater surfaces inspires human to design adhesives for wet tissue adhesion in surgeries. Characterization of mussel adhesive plaques describes a matrix of proteins containing 3,4-dihydroxyphenylalanine (DOPA), which provides strong adhesion in aquatic conditions. Several synthetic polymer systems have been developed based on this DOPA chemistry. Herein, a citrate-based tissue adhesives (POEC-d) was prepared by a facile one-pot melt polycondensation of two diols in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…For Glubran 2, the average shear and tensile strength in the current study is around twice the value reported by Kull et al BioGlue's shear strength was found to be very similar to that reported by Sidle and Maas . For Tisseel, the average shear and tensile strength found in our study was approximately one order of magnitude greater than that from Kull et al’s study but falls within the range of values reported elsewhere . The differences in tissue substrate are deemed to be the main factor explaining the differences.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For Glubran 2, the average shear and tensile strength in the current study is around twice the value reported by Kull et al BioGlue's shear strength was found to be very similar to that reported by Sidle and Maas . For Tisseel, the average shear and tensile strength found in our study was approximately one order of magnitude greater than that from Kull et al’s study but falls within the range of values reported elsewhere . The differences in tissue substrate are deemed to be the main factor explaining the differences.…”
Section: Discussionsupporting
confidence: 87%
“…21 The reported average adhesive strength in the literature for Tisseel ranges between 0.7 kPa and 15 kPa. 19,[21][22][23] For Glubran 2, the average shear and tensile strength in the current study is around twice the value reported by Kull et al 19 BioGlue's shear strength was found to be very similar to that reported by Sidle and Maas. 20 For Tisseel, the average shear and tensile strength found in our study was approximately one order of magnitude greater than that from Kull et al's study 19 but falls within the range of values reported elsewhere.…”
Section: Adhesive Strengthsupporting
confidence: 85%
See 1 more Smart Citation
“…Polydopamine is used for biomaterial surface modification because it is easy to obtain abundant active groups. These active groups are mostly phenolic hydroxyl/o-quinone and amino/imino for bimolecular immobilization on the material surface with minimal change in the chemical structure of biomaterials [38]. The plausible mechanism of polydopamine-induced-PEG coating is shown in Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…( A ) methyl-polyethylene glycol (PEG)-amine unit; ( B ) Immobilization of selenocystamine via polydopamine linker [38]; ( C ) Interfacial location of aminated PEG, polydopamine and hydroxyapatite [15]. …”
Section: Figurementioning
confidence: 99%